Effect of Concussion on Reaction Time and Neurocognitive Factors: Implications for Subsequent Lower Extremity Injury - Tyler Ray; Daniel Fleming; Daniel Le; Mallory Faherty; Carolyn Killelea; Jeffrey Bytomski; Tracy Ray; Larry Lemak; Corina Martinez; Michael F. Bergeron; Timothy Sell (International Journal of Sports Physical Therapy)
# Background